Naga people's (Tasikmalaya District, West Java, Indonesia) local knowledge of the variations and traditional management farm of village chickens - RUHYAT PARTASASMITA; JOHAN ISKANDAR; PUDJI MEILINDA RUKMANA (Society for Indonesian Biodiversity, 2017)
Partasasmita R, Iskandar J, Rukmana. 2017. Naga people's (Tasikmalaya District West Java, Indonesia) local knowledge of the variations and traditional management farm of village chickens. Biodiversitas 18: 834-843. There is a strong maintain on the traditional Sundanese traditions among the village people West Java in the modern agricultural and the livestock farming. For example, they have not adopted modern of race chickens with high external inputs, including chicken breeders, chicken foods, vitamins, antibiotics, and various modern medicines. Ordinarily, the consequence of this in a situation the village people have traditionally farmed the various village chickens based on local knowledge and strongly embed by culture. Recently, however, the traditional farming of the village chickens in many villages of West Java, has dramatically affected by rapid development of the introduction of commercial the modern race-chickens farming. As a result, the diversity of village chickens has dramatically decreased. In addition, the production system of the village chicken farm has extremely depended on external inputs. This paper discusses on local knowledge of Naga people of Tasikmalaya, West Java on variations and cultural practice among the Naga people in the managing of the village chicken farm. The method used in this study was mixed of qualitative and quantitative with the ethnozoological and ethnobiological approach. The result of the study shows that Naga people of Tasikmalaya, West Java has well-recognized variations of the village chickens which is based on the folk classification at the level specific and varietal. Until recently, the Naga people have traditionally managed the village chickens in the sustainable system due to economically viable, ecologically appropriate, and adaptable to socio-cultural traditions.